Comparison of diagnostic evaluations for cough among initiators of angiotensin converting enzyme inhibitors and angiotensin receptor blockers. Issue 5 (10th February 2016) - Gokhale, Mugdha; Girman, Cynthia; Chen, Yong; Pate, Virginia; Funk, Michele Jonsson; Stürmer, Til
Abstract: Purpose: Differential diagnostic evaluation associated with a drug may bias effect estimates because of an increased detection of preclinical outcomes. Persistent cough is a common side effect with angiotensin‐converting enzyme inhibitors (ACEI), and we hypothesized that ACEI initiators would undergo more diagnostic evaluations, potentially leading to diagnosis of preclinical lung cancer. We compared the incidence of cough‐related diagnostic evaluations and lung cancer among ACEI versus angiotensin receptor blockers (ARB) initiators. Methods: Using a 20% sample of Medicare claims 2007–2012, we identified initiators of ACEI or ARB, age 66–99 years. Incidence of diagnostic evaluation and lung cancer were compared using adjusted Cox models. Monthly probabilities of workup were compared using proportion differences. Results: There were 342 611 and 108 116 ACEI and ARB initiators, respectively. Monthly probability of chest X‐rays ranged from minimum 4.7% to maximum 21.2% in the 6 months pre and post‐initiation. Differences in incidence of diagnostic procedures in the 6 months after initiation were only minimal (chest X‐rays hazard ratio (HR) = 1.12; 95% CI: 1.10–1.14), chest‐MRI (0.86, 95% CI: 0.74–0.99), CT‐scans (1.09, 95% CI: 0.99–1.18) or bronchoscopies (1.03, 95% CI: 0.83–1.29). Proportion differences for chest X‐rays peaked in the month pre‐initiation (8.4%, 95% CI: 8.1–8.6) but negligible thereafter. There was no difference in the incidence of lung cancer among ACEI versus ARB initiators (HR = 0.99, 95% CI: 0.84–1.16). Conclusion: Results indicate minimal differential chest workup after ACEI versus ARB initiation and no difference in lung cancer incidence, but suggest differential workup in the month before the first recorded prescription. The latter may reflect drug use before the first observed pharmacy claim or increased workup before initiation of ACEI therapy. Copyright © 2016 John Wiley & Sons, Ltd.